Care at high‐volume centers is associated with improved outcomes for patients with pancreatic neuroendocrine tumors: A population‐level analysis. Issue 6 (11th March 2023) - Patel, Ranish K.; Sutton, Thomas L.; Schwantes, Issac R.; Behrens, Shay; Pommier, Rodney F.; Rocha, Flavio G.; Sheppard, Brett C.
Abstract: Background and Objectives: Primary resection and debulking of liver metastases have been associated with improved survival in pancreatic neuroendocrine tumors (PNETs). The treatment patterns and outcomes differences between low‐volume (LV) institutions and high‐volume (HV) institutions remains unstudied. Methods: A statewide cancer registry was queried for patients with nonfunctional PNET from 1997 to 2018. LV institutions were defined as treating <5 newly diagnosed patients with PNET per year, while HV institutions treated ≥5. Results: We identified 647 patients: 393 with locoregional ( n  = 236 HV care, n  = 157 LV care) and 254 with metastatic disease ( n  = 116 HV care, n  = 138 LV care). Patients with HV care had improved disease‐specific survival (DSS) compared to patients with LV care for both locoregional (median 63 vs. 32 months, p  < 0.001) and metastatic disease (median 25 vs. 12 months, p  < 0.001). In patients with metastatic disease, primary resection (hazard ratio [HR]: 0.55, p  = 0.003) and HV institution (HR: 0.63, p  = 0.002) were independently associated with improved DSS. Furthermore, diagnosis at a HV center was independently associated with higher odds of receiving primary site surgery (odds ratio [OR]: 2.59, p  = 0.01) and metastasectomy (OR: 2.51, p  = 0.03). Conclusions: Care at HV centers is associated with improved DSS in PNET. We recommend referral of all patients with PNETs to HV centers.